The lost opportunity from insufficient pollinators for global food supplies and human health. (October 2022) - Smith, Matthew R; Mueller, Nathaniel D; Springmann, Marco; Sulser, Timothy B; Garibaldi, Lucas A; Gerber, James; Wiebe, Keith; Myers, Samuel S
Abstract: Background: Animal pollination supports agricultural production for many healthy foods, such as fruits, vegetables, nuts, and legumes, which provide key nutrients and protect against non-communicable diseases. Today, most crops receive suboptimal pollination because of reduced abundance and diversity of pollinating insects. Methods: We modelled the effects on current global human health from insufficient pollination by quantifying the pollinator-related crop yield gap and lost consumption of pollination-dependent foods by country and region, after accounting for global trade, economic behaviours, and food waste. We also estimated the lost economic value of crop production for the following three diverse case-study countries: Honduras, Nepal, and Nigeria. Findings: Globally, we found that we are currently losing 3–5% of fruit, vegetable, and nut production per year because of inadequate pollination, leading to a median estimated 427 000 (95% uncertainty interval 86 000–691 000) excess deaths annually from lost healthy food consumption and associated diseases. Effects are unevenly distributed; lost food production is concentrated in low-income countries, while impacts on food consumption and mortality attributable to insufficient pollination are greater in middle-income and high-income countries with higher rates of non-communicable diseases. Furthermore, in our three case-study countries, we found that the economic value of crop production was 12–31% lower than if pollinators were abundant (because of crop production losses of 3–19%), mainly due to lost fruit and vegetable production. Interpretation: Insufficient populations of pollinators are responsible for large burdens of disease through lost healthy food consumption. Furthermore, low-income countries are losing substantial income and crop yields from pollinator deficits. These results underscore the urgent need to promote pollinator-friendly practices for both human health and agricultural livelihoods. Funding: Gordon & Betty Moore Foundation, Weston Foods, Fifth Generation, CGIAR, United States Agency for International Development, Bill & Melinda Gates Foundation, and Wellcome Trust.